Strain-specific transmission in an outbreak of ESBL-producing Enterobacteriaceae in the hemato-oncology care unit: a cohort study. Issue 1 (December 2017) - Uemura, Makiko; Imataki, Osamu; Uchida, Shumpei; Nakayama-Imaohji, Haruyuki; Ohue, Yukiko; Matsuka, Harumi; Mori, Hatsune; Dobashi, Hiroaki; Kuwahara, Tomomi; Kadowaki, Norimitsu
Abstract Background Extended-spectrum β-lactamase (ESBL)-producing bacteria are resistant to several types of antibiotics excluding carbapenems. A transmissibility of ESBL-producing Enterobacteriaceae would be depending on each bacterial property, however, that has not been elucidated in clinical setting. In this study, we attempted to identify the source of an outbreak of ESBL-producing bacteria in a medical oncology and immunology care unit. Methods An ESBL-producing Enterobacteriaceae (ESBL-E) outbreak observed between July 2012 and August 2012 in Kagawa University Hospital was surveyed using various molecular microbiology techniques. We used Pulsed-field gel electrophoresis (PFGE), PCR-based ESBL gene typing, and direct sequence of ESBL gene as molecular microbiology typing method to distinguish each strain. Results The typical prevalence of ESBL-E isolation in the unit was 7.0 per month (1.7 per week). The prevalence of ESBL-E isolation during the target research period was 20.0 per month (5.0 per week). In total, 19 isolates (11 K. pneumoniae and 8E. coli ) were obtained from clinical samples, including four control strains (two each of both bacteria), that were physically different from those obtained from other inpatient units in our hospital. Pulsed-field gel electrophoresis (PFGE) forK. pneumoniae (digested byXba I) produced similar patterns excluding one control strain. PCR classification of the ESBL gene forK. pneumoniae revealed that all strains other than the control strain carried SHV and CTX-M-9. This result was reconfirmed by direct DNA sequencing. Although the outbreak ofK. pneumoniae was considered to be "clonal, " PFGE and PCR classification of the ESBL genes forE. coli uncovered at least six different "non-clonal" strains possessing individual ESBL gene patterns. According to the result of an antibiogram, the pattern of antimicrobial susceptibility was more variable forK. pneumoniae than forE. coli . Conclusions Typing by PFGE and ESBL gene PCR analysis is practical for discriminating various organisms. In our cohort, two outbreaks were concomitantly spread with different transmission strategies, namely clonal and non-clonal, in the same unit. This might represent clinical evidence that transmissibility differs according to the type of strain. We speculated that patient-to-patient transmission of ESBL-E occurred according to the properties of each individual strain.